Perspective: Using Bronchiectasis Action Management Plans for Children With Bronchiectasis—Can It Improve Clinical Care? - Schutz, Kobi L.; Marchant, Julie M.; Chang, Anne B.; Turner, Catherine; Chatfield, Mark D.; McCallum, Gabrielle B. (Frontiers in Pediatrics, 2019)
While once thought to be rare, bronchiectasis has been increasing globally over the last 15 years. Bronchiectasis is a major contributor to chronic lung morbidity and mortality but remains a neglected disease in respiratory health globally. Currently, few high-level evidence-based management strategies are available for children with bronchiectasis. Strategies to improve clinical outcomes associated with exacerbations are important. In other respiratory conditions such as asthma and chronic obstructive pulmonary disease, use of personalized written management plans have been shown to improve clinical outcomes. Personalized management plans have also been recommended as part of treatment plans in adults with bronchiectasis. We thus undertook a review of the current literature to determine available evidence, and to establish whether a personalized written bronchiectasis action management plan (BAMP) improves clinical outcomes in children with bronchiectasis. Our search identified 43 articles; 16 duplicates were removed and a further 23 were excluded on titles and abstracts alone. Four full-text articles were reviewed but excluded. In the absence of any published studies, it remains unknown whether the use of BAMP is beneficial for improving clinical outcomes for children with bronchiectasis. These results have highlighted this clinical gap and identified the need for high-quality research to inform practice. Until high-quality evidence is available, clinicians are advised to adhere to current national and/or international guidelines.